2021
DOI: 10.1021/acs.langmuir.1c00605
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Polymer-Immobilized Polyimide Films Using Hot Pressing and Titania Coatings

Abstract: Recent studies have revealed that polymer molecules at film surfaces exhibit unique physical properties compared to those in bulk. On the other hand, such a topic has not been extensively focused for the cases of rigid polymers such as polyimide (PI). This study investigated whether hot pressing could induce the immobilization of other polymers, poly(4-vinylphenol) (PVP), on PI film surfaces. Results supported the immobilization of PVP on the PI film surfaces, and the increase of hot-press temperature resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…8c), by utilizing high temperature and pressure processing conditions. 308 Another example exploits hot pressing to enhance the electrical and thermal performance of conducting PEDOT:PSS films. 303 The performed experiments have suggested that the hot pressing induced significant changes in molecular conformations, with respect to the crystallite size and molecular orientation, that decreased the p-p stacking distance and thus, lowered the activation energy for charge carrier hopping, finally leading to more than 50% increase in electrical conductivity.…”
Section: -Published By the Royal Society Of Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…8c), by utilizing high temperature and pressure processing conditions. 308 Another example exploits hot pressing to enhance the electrical and thermal performance of conducting PEDOT:PSS films. 303 The performed experiments have suggested that the hot pressing induced significant changes in molecular conformations, with respect to the crystallite size and molecular orientation, that decreased the p-p stacking distance and thus, lowered the activation energy for charge carrier hopping, finally leading to more than 50% increase in electrical conductivity.…”
Section: -Published By the Royal Society Of Chemistrymentioning
confidence: 99%
“…More recently, hot pressing was employed in a variety of studies aiming to modify the microstructure of polymeric films and thus, to enhance their physical properties. 303,304,308,309 A clear example is the hot pressing of poly(4-vinylphenol) (PVP; see its chemical structure in the inset of Fig. 8b) on polyimide (PI), with the aim to obtain PVP-immobilized PI films.…”
Section: -Published By the Royal Society Of Chemistrymentioning
confidence: 99%
“…Synthetic polymers having lightweight and durable characteristics are currently one of the most widespread and essential materials used in daily life and various industries, markedly improving our quality of life. [1][2][3] On the other hand, recently, the environmental pollution of rivers and oceans due to polymer waste that accompanies the mass consumption of synthetic polymers has become apparent on a global scale. 4,5 The causes of plastic and rubber waste are diverse, for example, physical wear and tear during the laundering of clothes and the use of fishing nets, tire wear while driving, and failure to collect single-use packages and used devices.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, various surface modification methods for polymer materials have been developed. These are mainly categorized into physical and chemical methods. An example of the former approach is a plasma-based treatment allowing the surface to be generally hydrophilic. Energetic ionized species generated from gaseous oxygen attack the polymer surface, where functional groups such as hydroxy, carbonyl, and carboxylic acid groups that contribute to the increase in free energy are generated.…”
Section: Introductionmentioning
confidence: 99%